Drivers of ecosystem service specialization in a smallholder agricultural landscape of the Global South: a case study in Ethiopia - Brück, Maria; Fischer, Joern; Law, Elizabeth A.; Schultner, Jannik; Abson, David J. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
The global shift toward agricultural specialization in the 20th century led to unprecedented ecological and socioeconomic changes, both positive and negative, in rural landscapes. Economic theory describes comparative advantage and market participation as two important drivers of such changes. Landscapes in the Global South are still often characterized by subsistence agriculture and direct dependence on natural ecosystem processes. Agricultural specialization is part of the structural transformation process from subsistence to market-oriented agriculture. However, comparative advantage and market participation as major drivers for agricultural specialization remain understudied. In this paper, we assess the potential drivers of ecosystem service specialization in an Ethiopian smallholder landscape at the kebele level, the smallest administrative unit in Ethiopia. We measured specialization via the concentration of production for a range of locally important provisioning ecosystem services (beef, cattle, coffee, eucalyptus, honey, maize, sorghum, and teff). We measured comparative advantage based on productivity data, and assessed spatial flows of ecosystem services to local, regional, and global markets (i.e., telecoupling). To unpack the relationships between specialization, comparative advantage, and telecoupling, we used hierarchical clustering, principal component analysis, correlation analysis, and linear regression. More telecoupled kebeles (i.e., kebeles that produced more of ecosystem services that flow to broader spatial scales) were more specialized in their ecosystem service production, and the positive relationship between comparative advantage and specialization grew stronger with altitude. Wealthier kebeles and kebeles with higher population density were less specialized. Biophysical drivers, such as altitude and amount of forest cover, influenced the ecosystem services produced and the relationship between comparative advantage and specialization. Policy makers should therefore try to balance potential positive and negative consequences of specialization, and to account for fine-scale social and biophysical drivers underpinning diverse ecosystem service production profiles.
Keywords: Agriculture; Specialization; Advantage; Ecosystem; Service Provision; Ethiopia; Land Management; Smallholder Structures